Government teachers, private tutors and primary education in Colonial Delhi, 1910-1947 - Akanshi Vidyarthi (International Journal on Orange Technologies, 2020)
Teacher and certification were two major institutions used subtly by the colonial rule to legitimise their superiority, governance and authority over the colonial masses. Moreover, they were also used very explicitly to marginalise the indigenous education system. Active attempts were made on the part of colonial administrators to train the teachers. These teachers were to act as the agents to translate British culture, knowledge and education as superior and scientific as contrast to the indigenous forms of learning. The colonial education system barged through the young minds through the new instructor i.e., the newly trained teacher. The article consists of two parts. The first part looks into the role of the newly trained teacher and their influence in legitimising colonial pedagogy. Secondly, it talks about the trend of resorting to private tutor to keep pace with the rapidly changing education.